2019
DOI: 10.1002/ddr.21593
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of mitochondrial permeability transition pore inhibitors

Abstract: It is now firmly established that an important event in the formation of reperfusion injury of the heart is the opening of mitochondrial permeability transition pores (mPTPs), which changes the permeability of the mitochondria. mPTP opening results in the death of cardiomyocytes through activation of apoptosis and necroptosis. Experimental studies have shown that pharmacological inhibition of mPTP opening promotes the reduction in the infarct size and the suppression of apoptosis. Indeed, studies have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 180 publications
(268 reference statements)
0
15
0
Order By: Relevance
“…The opening of mPTP is a vital event that causes cell death . To elucidate the underlying mechanism of complex-induced apoptosis, we explored its possible effects on mitochondrial functions.…”
Section: Resultsmentioning
confidence: 99%
“…The opening of mPTP is a vital event that causes cell death . To elucidate the underlying mechanism of complex-induced apoptosis, we explored its possible effects on mitochondrial functions.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, MMP and mitochondrial ca 2+ concentrations are the principal drivers of mPTP opening, resulting in the release of cytochrome c and other substances associated with cell death into the cytosol (191,192,(194)(195)(196)(197). This leads to mitochondrial swelling and reduced mitochondrial respiratory chain activity, which can cause various diseases, such as neurodegenerative diseases and cancers (190,(198)(199)(200). Furthermore, studies have shown that PINK1 can inhibit mPTP opening by downregulating intracellular ROS levels, suggesting that mitochondrial autophagy serves a regulatory role in mPTP opening (191)(192)(193).…”
Section: Detection Of Mitochondrial Permeability Transition Poresmentioning
confidence: 99%
“…105 MPT pore opining induces apoptosis of cardiomyocytes, MPT pore closing prevents ischemic/reperfusion injury of the heart. 162 It has been shown that the cardioprotective effect of BNP at cardiac reperfusion is mediated via MPT pore closing. 73 There are data that ANP prevents MPT pore opening in H9c2 cardiomyoblasts.…”
Section: Natriuretic Peptides K Atp Channels and Mpt Porementioning
confidence: 99%